"Dr House" - gra i semiologia - Kloch, Zbigniew (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2012)
The paper describes how the characters of House, M.D. interact and relate to each other; it also discusses the role played by specific, semantically charged means of constructing narration. On one hand, the show largely maintains the model of a conventional medical drama, on the other, it deconstructs many of the characteristics inherent in the genre. The paper also attempts to explain the show’s huge popularity (for a certain time in the United States alone it reached 27 million viewers) achieved in spite of going beyond what an average viewer would expect, primarily by the show’s construction and by evoking ideas outside a classic medical drama.

Esej o znanym serialu telewizyjnym jest analiza jego światowej popularności i jego poetyki jako przemyślanej konstrukcji tekstowej. Serial po części realizuje, zaś większym stopniu burzy konwencje typowej opowieści szpitalnej, nad którą nadbudowuje się diagnozę dotyczącą jednostki, jej relacji z innym i otoczeniem społecznym.
House, M.D. – Interplay and Semiology
Zbigniew Kloch, Instytut Badań Literackich PAN, Uniwersytet Warszawski, "Dr House" - gra i semiologia, House, M.D. – Interplay and Semiology, „Images” 2012, vol. X: Microcosmos, red. A. Szpulak i W. Otto, nr 19, s. 154-162., ISSN 1731-450x, język: polski
Keywords: House, M.D; Semiology; Interplay; Narration; Medical Drama; Deconstruction of Genre; serial medyczny; semiologia; znak; narracja filmowa; schemat konstrukcyjny; bohater